2015 Tax-Competitiveness Report: Canada is Losing its Attractiveness - Philip Bazel; Jack M. Mintz (The School of Public Policy Publications, 2016)
It can be easy for Canadians who appreciate the qualities of their country to overestimate the power that it also has to lure investment in a world where so many other destinations are competing for capital. Canadians can take pride in our political stability and our highly educated workforce, and we do have good communication and transportation infrastructure, but a great number of other countries offer those things, too, at roughly the same level. Meanwhile, Canada suffers in the eyes of investors for being a relatively small market, distant from large export destinations, with a cold climate and geographic vastness that only raise the cost of doing business here. Canada has been able to overcome its disadvantages in recent years largely by being highly competitive on business taxes. Unfortunately, the tendency of Canadian provincial and federal governments lately to raise taxes on business has been rapidly erasing that slight advantage. Dangerously, Canada is beginning to lose its competitive edge. It is difficult enough in a world of slower global growth to attract investment, but some major economies with whom Canada directly competes for investment have recognized the need in this challenging environment to make themselves even more attractive to investors. It is true that some countries, such as Belgium, Chile, Brazil, Greece and India have, like Canada, enacted certain policies — primarily higher business taxes — that have increased their marginal effective tax rate (METR). Still, other important peer countries have been working to lower theirs; notably Denmark, Japan, France, Portugal, Switzerland and the U.K. As a result of their cuts, and because of changes to policies in Canada that have increased METRs here, Canada has sunk from having the 16th-highest burden on capital in the OECD (which was at least in the middle of the pack) to having the 13th highest. We now have the sixth-highest rather than lowest METR in the G7. In a compilation of 92 countries, Canada finds itself in the middle of the pack with the 35th highest tax burden on capital. The blame for this is shared by provincial and federal governments. In recent years, governments in Newfoundland and Labrador, New Brunswick, Alberta and B.C. have all raised business taxes (Alberta now has a higher corporate income tax than B.C. Ontario or Quebec). Quebec has scaled back incentives for investors, Manitoba increased its sales tax, and B.C. eliminated the harmonized sales tax, reintroducing the burden on business inputs implicit in the provincial retail sales tax. With the U.S. election of Donald Trump and a Republican Congress promising to reduce corporate income tax rates, as well as the recent affirmation by British Prime Minister Theresa May to lower the U.K. corporate income tax rate to 17 per cent, the pressure will be to reduce, not increase corporate income taxes in the next several years. Should the U.S. dramatically reduce its corporate tax rate, Canada will lose its business tax advantage altogether. Just as concerning, Canada has created a tax system that discriminates against the service sector, including transportation, communications, construction, trade, and business and financial services, all of which are among the fastest-growing sectors, and play a key role in facilitating innovation, infrastructure and trade. Canada’s tax policies continue to favour slower-growing sectors, namely manufacturing and resources. The good news is that Canada can regain competitiveness without drastic tax reform. It is clear that there needs to be greater neutrality among sectors so that service industries are not discriminated against (the same is true for large businesses versus small businesses). Meanwhile, those provinces that still have a retail sales tax can improve their attractiveness by moving to the HST, as other provinces have. The federal government is also in the midst of reviewing subsidies and other tax expenditures that create an unlevel playing field. However, instead of spending that money as it plans to, it should consider Canada’s falling competitiveness and use the revenues to lower the corporate income tax. With the savings, it could afford to cut that tax from 15 to 13 per cent, not only remaining revenue neutral, but likely actually increasing the corporate tax base in the process.